Interfacing arrangement and software development for acquisition and analysis of respiratory data - Akter, Nasreeen (BRAC University, 2010)
Lung diseases are still major killers in Bangladesh due to absence of proper diagnostic equipment primarily because of high cost. Indigenous development of transducer, hardware interface and application software can bring the benefit of modern technology at the doorstep of the people. In this respect, computerisation of a mechanical spirometer is an attempt to make the dream of poor people into reality. A wedge bellow type spirometer as transducer, modified ISA card circuit with low cost arrangement for hardware interface and window based easy operating software have been developed to reach to the target.